Case report: Hemophagocytic lymphohistiocytosis complicated by multiple organ dysfunction syndrome following aseptic encephalitis - Chen, Quan-Ting; Chen, Ming-Hua; Lin, Yu-Kai; Yeh, Ren-Hua; Lu, Chun-Chi; Hsiao, Po-Jen; Sung, Yueh-Feng (Frontiers in Immunology, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a rare but potentially life-threatening condition caused by excessive immune activation. Secondary HLH is usually triggered by infection, most often from viral infection or malignancy. Here, we present a case of secondary HLH, complicated by multiple organ dysfunction syndrome triggered by critical aseptic encephalitis. A 27-year-old man without any underlying disease presented to our hospital with fever, disturbance of consciousness, and generalized seizures. The patient was diagnosed with aseptic encephalitis with super-refractory status epilepticus. Although antiseizure medications and immunoglobulins were administered, the patient developed multiple organ dysfunction syndrome. HLH was later diagnosed based on hypertriglyceridemia, hyperferritinemia, splenomegaly, cytopenia, and phagocytosis of nucleated cells, as shown by a blood smear of bone marrow aspiration. Treatment with pulse steroid therapy and plasmapheresis was initiated rather than chemotherapy because of the patient’s critical condition. However, the patient died of profound shock and multiple organ failure. Diagnosis of HLH is challenging in patients with severe infections because of similar clinical manifestations and laboratory findings. The early recognition of HLH provides patients with the opportunity to receive appropriate treatment, which can lead to increased survival and remission rates.